STRATEGI PENYUSUNAN ANGGARAN BAHAN BAKU DALAM MENINGKATKAN EFISIENSI PRODUKSI PERUSAHAAN - Dini Vientiany; Miranti Agustina; Annisa Afwani; Khaila Calsa Fhadillah (INTERNATIONAL, Journal of Sharia Business Management, 2025)
Production efficiency is a crucial factor in improving company performance and competitiveness, particularly in manufacturing companies that rely heavily on raw material cost management. The raw material budget serves as a tool for planning and controlling production costs to ensure effective and efficient production processes. This study aims to analyze the role and strategies of raw material budgeting in improving company production efficiency. The research method used is a literature review with a descriptive qualitative approach. Data were obtained from textbooks, national and international journals, and relevant scientific articles, then analyzed using a SWOT analysis. The results show that the raw material budget has the strength to improve cost control and production efficiency, but still has the weakness of relying on historical data. Opportunities for utilizing information technology can improve budget accuracy, while fluctuations in raw material prices are a major threat. Adaptive budgeting strategies are needed to support sustainable production efficiency.